IMPLEMENTASI SISTEM BACKUP DATABASE MYSQL OTOMATIS MENGGUNAKAN MYSQLDUMP DAN CRON JOB PADA INFRASTRUKTUR CLOUD - Endro Dwi Wuryanto; Setya mulyo Utomo (UNIVERSITAS STEKOM, 2026)
Data availability is a crucial aspect of modern information system management. Data loss due to hardware failure, user error, or cyberattacks can disrupt company operations. Sinarbit, as a provider of software, hosting, database, and technical support services, requires an automated backup mechanism to ensure customer data security. This study aims to implement an automated MySQL database backup system using the mysqldump utility, gzip compression, and Cron Job scheduling on a Linux server. The research methods used include requirements analysis, backup system design, automation script implementation, and database backup and restore success testing. The results showed that the backup script was successfully run 28 times. Gzip compression successfully reduced the backup file size by an average of 75% compared to the original database size. However, the extraction process was not successful for all data because only 25 valid files were successfully extracted, while 3 files experienced CRC errors, resulting in a restoreable backup success rate of 89%. Based on these results, the implemented automated backup system is able to improve the reliability, security, and availability of data on Sinarbit's service infrastructure.